2022
DOI: 10.5937/ekopolj2202469v
|View full text |Cite
|
Sign up to set email alerts
|

Consumer's characteristics and attitudes towards organic food products in times of Covid-19 pandemic

Abstract: The pandemic caused by the Covid-19 virus significantly affected the consumers' behavior. The subject of the paper is to analyze the consumer characteristics, the consumer attitudes towards organic food products, as well as the changes in the consumer behavior. The research was performed in 2021 in the Republic of Serbia. The statistical software package SPSS has been utilized for data analysis. Our findings show that, in times of COVID-19 pandemic, the consumers have a very positive perception of nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The fact is that many of these sustainable farming systems were firstly being adopted by NGOs, small farmers and, more recently, by large commercial companies. Various studies have confirmed that there is a positive attitude towards the consumption of products that come as a result of sustainable production [48][49][50][51]. Organic farming can contribute to sustainable development by showing the model of production or being the lighthouse for sustainability.…”
Section: Contribution Of Organic Agriculture To Sustainable Developme...mentioning
confidence: 99%
“…The fact is that many of these sustainable farming systems were firstly being adopted by NGOs, small farmers and, more recently, by large commercial companies. Various studies have confirmed that there is a positive attitude towards the consumption of products that come as a result of sustainable production [48][49][50][51]. Organic farming can contribute to sustainable development by showing the model of production or being the lighthouse for sustainability.…”
Section: Contribution Of Organic Agriculture To Sustainable Developme...mentioning
confidence: 99%